Cognitive Impairments and Risk Factors After Ruptured Anterior Communicating Artery Aneurysm Treatment in Low-Grade Patients Without Severe Complications: A Multicenter Retrospective Study - Ma, Ning; Feng, Xin; Wu, Zhongxue; Wang, Daming; Liu, Aihua (Frontiers in Neurology, 2021)
Background Cognitive impairment is the main reason affecting quality of life in patients with low-grade aneurysmal subarachnoid hemorrhage. Objective We explored cognitive impairments and risk factors after treatment for ruptured anterior communicating artery (AComA) aneurysms in low-grade (Hunt-Hess grade of 1-3) patients without severe complications. Methods 126 patients with Hunt-Hess grade of 1-3 who underwent endovascular embolization or microsurgical clipping for ruptured AComA aneurysm treatment at three academic institutions in China from January 2015 to December 2017 were assessed with the modified Telephone Interview for Cognitive Status (TICS-m), the modified Rankin Scale (mRS), and the instrumental activities of daily living (IADL) scale two or more years after microsurgical clipping or endovascular coiling. Multiple cox-regression analysis was used to identify variables independently associated with cognitive impairment. Results Of the total of 126 patients, 115 (91.3%) achieved good clinical outcomes (mRS score 0-2) and 109 (86.5%) had excellent quality of life (IADL score 8). Twenty-eight (22.2%) patients showed cognitive impairments (TICS-m≤27). The multivariate COX regression analysis showed that the female patients and longer duration of loss of consciousness at onset of subarachnoid hemorrhage (SAH) were independently associated with cognitive impairment. Cognitive outcome at the latest follow-up was not significantly different between patients treated after surgical clipping and coiling. Conclusion About one in five patients showed cognitive impairments after treatment for ruptured AComA aneurysms. Patients who is female sex, and longer duration of loss of consciousness at onset of SAH may be at risk of cognitive impairment.